Work Environment and Work Stress Towards Employee Performance PT Lezax Nesia Jaya Kota Yogyakarta - Alfreda Bagus Prasetyo; Ignatius Soni Kurniawan; Eko Yulianto (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2025)
This study aims to examine how the physical work environment, non-physical work environment, and work stress affect employee performance at PT Lezax Nesia Jaya in Yogyakarta City. The study employs a quantitative method using questionnaires distributed through accidental sampling to a total of 60 respondents, calculated using the Slovin formula. The data obtained were then processed using SPSS 26 software. The analysis results reveal that the physical work environment, non-physical work environment, and work stress have a significant positive effect on employee performance. The findings from this study can serve as a reference for other researchers who wish to further explore employee performance. Additionally, the results provide information that can be used by the company as a basis for developing policies focused on improving employee performance.